After cancer: a new way of living - Salci, Maria Aparecida; Marcon, Sônia Silva (Rev Rene, 2011)
Cancer is a disease that endangers life, making people reflect on various aspects of life that were not prized or were taken for granted before the illness. The objective of this study was to know the changes occurred in the lives of the women and their families after living with cancer. This is a descriptive-exploratory study of qualitative nature, carried out in 2005 in Maringá-PR, with twenty individuals, comprising ten women suffering from cancer, and their relatives. The interview consisted of a series of open-ended questions. It was found out that when undergoing experiences with a serious disease like cancer, many people start to rearrange their lives with new strategies, new values, giving new meanings to past events and perceptions. The outstanding issues are related to changes in health habits, daily tasks, life philosophy and faith. It was concluded that health professionals should be aware of the different phases imposed by the disease in the family, in order to act as a support source and provide psychological help to families that face cancer.